Enforcement of Islamic Finance Contracts: A Comparative Study of Common Law And Shari’ah Court - Olaitan Abdulkabir Oladapo (Penerbit Hellow Pustaka, 2024)
It is unarguably that Islamic finance is a fast-growing financial system that left everyone in bewilderment. Despite the blows of resistance to its growth, Islamic finance has grown to involve over three hundred financial institutions in both Muslim countries and international financial markets for the past three decades (Rodney, 2002). More than 50 Islamic Financial Institutions among the 600 institutions in the world today are situated in Africa (ICD, 2015 report). Coming down to Nigeria, an estimated size of United States Dollars (USD) 2.3 billion was recorded from the Islamic finance industry in 2021 (Amarachi and Ibrahim). Proponents of Islamic finance viewed the growth of Islamic finance as an “explosion”, describing it as the rise of Islam and an important trend in global finance (Umar and Ahmad, 2009). Despite all the business opportunities that Islamic finance proffers, enforcement of agreements arising out of Islamic finance principles especially in courts of common law origin poses a major hindrance to the speedy growth of Islamic finance across the globe with Nigeria as a case study. Employing a doctrinal methodology, this paper envisages that with proper orientation of customers and business people about the prospects of Islamic finance as an ethical and interest-free financial system, positive approach to Islamic finance by members of the public, acting within the scope of Shari’ah principles by parties to Islamic finance contracts and governmental supports together with conducive operational and legal frameworks, a progressive Islamic finance administration can be sustained in the society.